Effect of different timing of letrozole initiation on pregnancy outcome in polycystic ovary syndrome - Shi, Lan; Ye, Shujin; Gao, Mengyun; Chen, Yijie; Jin, Xuejing; Zhang, Zhifen (Frontiers in Endocrinology, 2022)
To investigate the efficacy of oral letrozole starting on day 3 or 5 of the menstrual cycle in patients with PCOS. we analyzed patients who received oral LE for OI at the Hangzhou Women’s Hospital from January 2016 to January 2021. 539 PCOS patients with fertility requirements were classified into the D3 group and D5 group according to the different starting times of oral LE, from the 3rd or 5th day of the menstrual cycle or LE is taken orally for 5 days starting on day 3 or 5 of progesterone withdrawal bleeding. Treatment started with one tablet (LE 2.5 mg), continue the regimen from the previous cycle in non-responders and continued until pregnancy or for up to three ovulatory cycles, with visits to determine ovulation and pregnancy, followed by tracking of pregnancies. The primary outcome was to compare ovulation rates, conception rates, live birth rates, pregnancy complications, and pregnancy outcomes at different initiation times.Women who started LE on the 5th day of their menstrual cycle had more cumulative conception rates than those who started LE on the 3rd day（173 of 228[75.9%]vs. 201 of 311[64.6%], P= 0.005; rate ratio for conception, 1.174; 95% confidence interval,1.052 to 1.311) without significant differences in overall live birth rate, though there were 142 of 228[62.3%] in the D5 group versus 172 of 311[55.3%] in the D3 group (P= 0.105). The median (IQR) endometrial thickness was significantly (P = 0.013) greater during the D5 group treatment compared to the D3 group, which may be related to higher conception and clinical pregnancy rates. The median maximum follicle diameter was not statistically (P = 0.073) different between the two groups. The cumulative ovulation per cycle rate was higher with D5 than with D3 (287 of 405 treatment cycles [70.9%] vs. 388 of 640 treatment cycles [60.6%], P=0.001). There were no significant between-group differences in pregnancy loss (31 of 173 conceptions in the D5 group [17.9%] and 29 of 201 conceptions in the D3 group [14.4%]) or multiples pregnancy (8.2% and 10.5%, respectively). Rates of other adverse events during pregnancy were similar in the two treatment groups.